2009
DOI: 10.1007/s10555-008-9170-7
|View full text |Cite
|
Sign up to set email alerts
|

Rho signaling, ROCK and mDia1, in transformation, metastasis and invasion

Abstract: The Rho subgroup of the Rho GTPases consisting of RhoA, RhoB and RhoC induces a specific type of actin cytoskeleton and carry out a variety of functions in the cell. mDia and ROCK are downstream effectors of Rho mediating Rho action on the actin cytoskeleton; mDia produces actin filaments by nucleation and polymerization and ROCK activate myosin to cross-link them for induction of actomyosin bundles and contractility. mDia is potentially linked to Rac activation and membrane ruffle formation through c-Srcinduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
433
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(448 citation statements)
references
References 82 publications
13
433
0
2
Order By: Relevance
“…Thus, it seems that strict regulation of Cdc42 and Rac1, by their upstream regulators, is crucial for podosome organization. It has been shown that Src activates Rac1 through the Cas-Crk-DOCK180 complex and RhoA-Dia1 signaling (Narumiya et al, 2009). Taken together, these findings suggest that an appropriate interplay between these Rho family GTPases is involved in podosome formation and that the Src-Arhgef5-RhoA axis has a triggering role in the pathway leading to podosome formation.…”
Section: Arhgef5 In Podosome Formationmentioning
confidence: 76%
“…Thus, it seems that strict regulation of Cdc42 and Rac1, by their upstream regulators, is crucial for podosome organization. It has been shown that Src activates Rac1 through the Cas-Crk-DOCK180 complex and RhoA-Dia1 signaling (Narumiya et al, 2009). Taken together, these findings suggest that an appropriate interplay between these Rho family GTPases is involved in podosome formation and that the Src-Arhgef5-RhoA axis has a triggering role in the pathway leading to podosome formation.…”
Section: Arhgef5 In Podosome Formationmentioning
confidence: 76%
“…Mammalian diaphanous (mDia) is a formin protein that is activated upon Rho binding, resulting in nucleation of new actin filaments and polymerization that generates unbranched filaments, which is important in the formation of stress fiber contractile units. [23][24][25] Active RhoA recruits profilin, which binds G-actin to facilitate F-actin barbed end polymerization. 26 Phosphorylation of cofilin by LIM kinase results in a loss of cofilin activity and stabilization of actin filaments, which is the end result of RhoA-mediated activation of ROCK and, subsequently, of LIM kinase, the socalled RhoA-ROCK-LIM kinase-cofilin pathway.…”
Section: The Central Regulator Of Cellular Contractility: Rhoamentioning
confidence: 99%
“…Firstly, it activates myosin II contraction, through its effector Rho Kinase, which provides the forces required to retract the spread margins of the cell, pulling the bulk of the cell upwards to from a sphere [16]. Secondly, based on its function in other contexts, RhoA likely helps to drive actin filament formation through the activation of a formin, mDia1 [24]. As a result, mitotic cells lacking Ect2, which have severely decreased RhoA activity, are much flatter, with a soft, disorganized actin cortex and associated spindle defects [16].…”
Section: Ect2 and Erm Proteins In Mitotic Rounding And Cancer Metastasismentioning
confidence: 99%